2003
DOI: 10.1051/0004-6361:20030034
|View full text |Cite
|
Sign up to set email alerts
|

Gas kinematics of a sample of five Hickson Compact Groups

Abstract: Abstract. We present Fabry Perot observations of galaxies in five Hickson Compact Groups: HCG 10, HCG 19, HCG 87, HCG 91 and HCG 96. We observed a total of 15 galaxies and we have detected ionized gas for 13 of them. We were able to derive 2D velocity, monochromatic, continuum maps and rotation curves for the 13 objects. Almost all galaxies in this study are late-type systems; only HCG 19a is an elliptical galaxy. We can see a trend of kinematic evolution within a group and among different groups -from strongl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
76
3

Year Published

2004
2004
2010
2010

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(89 citation statements)
references
References 36 publications
10
76
3
Order By: Relevance
“…This is confirmed by a number of studies that have shown distorted kinematics and morphologies of compact group galaxies (e.g. Presotto et al 2010;Amram et al 2007;Coziol & Plauchu-Frayn 2007;Amram et al 2003;Plana et al 2003Plana et al , 1998, also by studies of groups containing HI tidal debris (Verdes-Montenegro et al 2001) and newly formed stars forming systems outside the luminous member galaxies (e.g. de Mello et al 2008), as well as studies of diffuse light presumably originated from stripped material from the outskirts of galaxies in compact groups (e.g.…”
Section: Outliers From the Tf Relationmentioning
confidence: 60%
See 4 more Smart Citations
“…This is confirmed by a number of studies that have shown distorted kinematics and morphologies of compact group galaxies (e.g. Presotto et al 2010;Amram et al 2007;Coziol & Plauchu-Frayn 2007;Amram et al 2003;Plana et al 2003Plana et al , 1998, also by studies of groups containing HI tidal debris (Verdes-Montenegro et al 2001) and newly formed stars forming systems outside the luminous member galaxies (e.g. de Mello et al 2008), as well as studies of diffuse light presumably originated from stripped material from the outskirts of galaxies in compact groups (e.g.…”
Section: Outliers From the Tf Relationmentioning
confidence: 60%
“…The present study complements the sample of compact group galaxies with measured velocity maps presented by Plana et al (1998Plana et al ( , 2000Plana et al ( , 2003, Mendes de Oliveira et al (1998), Amram et al (2003Amram et al ( , 2004Amram et al ( , 2007, and Torres-Flores et al (2009). We present for the first time velocity maps for galaxies in nine Hickson compact groups (HCGs 37,40,47,49,54,56,68,79,and 93.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations